2001
DOI: 10.2337/diabetes.50.3.622
|View full text |Cite
|
Sign up to set email alerts
|

Glucokinase Gene Locus Transgenic Mice Are Resistant to the Development of Obesity-Induced Type 2 Diabetes

Abstract: Transgenic mice that overexpress the entire glucokinase (GK) gene locus have been previously shown to be mildly hypoglycemic and to have improved tolerance to glucose. To determine whether increased GK might also prevent or diminish diabetes in diet-induced obese animals, we examined the effect of feeding these mice a high-fat high-simple carbohydrate low-fiber diet (HF diet) for 30 weeks. In response to this diet, both normal and transgenic mice became obese and had similar BMIs (5.3 ؎ 0.1 and 5.0 ؎ 0.1 kg/m … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
37
1
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 87 publications
4
37
1
1
Order By: Relevance
“…In contrast, overexpression of one copy of the GK gene slightly lowers hyperglycaemia and hyperinsulinaemia induced by a high-fat diet [9]. However, these mice also overexpressed GK in beta cells [18] whereas in the present study, transgenic mice specifically overexpressed GK in the liver.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…In contrast, overexpression of one copy of the GK gene slightly lowers hyperglycaemia and hyperinsulinaemia induced by a high-fat diet [9]. However, these mice also overexpressed GK in beta cells [18] whereas in the present study, transgenic mice specifically overexpressed GK in the liver.…”
Section: Discussionmentioning
confidence: 50%
“…This leads to normalization of blood glucose in the absence of insulin [8]. Furthermore, a high-fat diet did not induce diabetes in transgenic mice overexpressing one copy of the GK gene [9]. In these mice, hepatic GK overexpression reduced hyperglycaemia and hyperinsulinaemia induced by a high-fat diet.…”
Section: Resultsmentioning
confidence: 92%
“…Hyperglycaemia is the main factor responsible for the development of diabetes-associated retinal, renal, neurological and vascular complications [25]. Overexpression of GK in the liver of transgenic mice has been shown to prevent the development of streptozotocin-induced diabetic alterations or high-fat dietinduced hyperglycaemia [15,16,17]. Moreover, mice carrying liver-specific GK gene disruption showed decreased hepatic glucose uptake and were moderately hyperglycaemic [26].…”
Section: Discussionmentioning
confidence: 99%
“…These transgenic mice showed lower fasting blood glucose concentrations, improved glucose tolerance and increased glycogen synthesis in the liver as compared to wild-type (wt) mice. More importantly, it was shown that GK overexpression in the liver prevents the development of hyperglycaemia or diabetes induced by streptozotocin or a high-fat diet [15,16,17].…”
mentioning
confidence: 99%
“…Decreased expression of Glucokinase (-1.93 fold) is also associated with hyperglycemia and IGT. 32 Nfyb, a transcription factor which promotes basal transcription of rat pyruvate carboxylase gene in β-cells, also showed an increase in the present study, and the mechanism needs to be understood. Retinoic Acid (RA) well characterized differentiation agent is known to improve pancreatic β-cells function in the following ways: (1) facilitating glucose stimulated insulin release in vitamin A depleted rats, 33 (2) induces biphasic glucose stimulated insulin secretion in human fetal pancreas explants, 33 (3) enhances insulin production in insulin secreting cell lines, 33 (4) increases glucokinase activity and gene expression levels in primary rat islets culture and insulinoma cell lines.…”
Section: Resultsmentioning
confidence: 93%